Applying Collaborative Learning to Improve Students’ Academic Presentation Skills and To Develop Their Self-Confidence - Iyehezkiel Parudani (ISJN Journal, 2022)
It is a challenge to teach academic skills of the students of Academic Presentation as it comprises a wide range of language skills, critical thinking skills and even psychological aspects as students often have non-linguistic problems that they need to overcome to be able to deliver their presentations successfully. Students often come to this class with an intermediate or even pre-intermediate competence in English which makes it difficult for them to put their ideas in to words. Due to a lack of self-confidence in their English language skills, some students revert to using material taken directly from the internet or other resources which results in plagiarism. This research aims to apply the collaborative learning approach in the instruction of academic presentation skills to help students develop their presentations skills, build their confidence and reduce plagiarism when presenting their materials. This is a quasi-experimental study which will make use of both quantitative and qualitative methods. The subjects are students of the English Study Program Pamulang University who are in their third semester. The subjects in one class will be taught the course using collaborative learning and the other parallel class will be taught using the conventional approach. Quantitative data will be collected through a questionnaire and post-test and qualitative data will be collected through class observations, log-sheets and students’ reflections. Interviews will be held to clarify any issues encountered in the collaborative learning process.